PENGEMBANGAN PENUNTUN PRAKTIKUM IPA INOVATIF UNTUK SMP/MTs KELAS VIII SESUAI KURIKULUM 2013 Se-KABUPATEN TAPANULI TENGAH - Bronika Septiani Sianturi; Jhonas Dongoran (Universitas Negeri Medan, 2020)
This research was conducted to develop an integrated science practicum guide with the theme of inquiry-based photosynthesis for junior high school students with student learning outcomes and activities. This research is a Research and Development research with small-scale trials in class VIII A and large scale at VIIIB. The results showed that the practical guide was valid and feasible to use by obtaining an average score of> 3.2 from each expert. After calculating the n gain formula, the classical gain n value is 0.56 (moderate), with the classical completeness percentage is 100%. The results of the analysis of students' understanding using practicum guides have been developed with an average of 83.84. Meanwhile, the understanding of students who did not use the practicum guide that had been developed obtained an average of 62.20. This shows that the understanding of students using the practicum guide that was developed is higher than without using the practicum guide that has been developed. The results of student activity increased after the second meeting with an average of 85.47% of students belonging to the